Coping Strategies of the Urban Poor: A Case Study From Ghana. Issue 3 (11th September 2020) - Ofori‐Boateng, Kenneth; Adams, Samuel; Ohemeng, Williams
Abstract : The study examines the profile and livelihood strategies of the urban poor. Utilizing the primary data from three selected poverty prone areas in Accra, the study traces the migratory history of 216 poor urbanized youth and solicits how they cope with an urban livelihood. The findings show that respondents did not receive any formal social protection and informal support from family, and social clubs/associations were also minimal. Coping strategies adopted by these respondents included: petty trading (36.2 percent), street "kayayee" (kayaye is a local name given to head porters/truck pushers for a fee. It a common feature at the Central Business District of Accra; 25.5 percent), street hawking (12.8 percent), and truck pushing (10.6 percent). Some also get involved in illegal and immoral activities such as theft (in the case of males) and prostitution (in the case of the females). It is recommended that since most of them are school dropouts and above the age of availing themselves to the new free senior high school education being implemented by the government, both formal and informal skills (apprenticeship), and vocational training should be rigorously and diligently pursued to lift them out of poverty.